Pengembangan Media Pembelajaran Interaktif pada Materi Bioteknologi Modern Menggunakan Articulate Storyline 3: Media Pembelajaran Interaktif - Hasibuan, Safrina Rizkiah; Diningrat, Diky Setya (Universitas Garut, 2025)
The teaching media currently used is still limited to printed materials, which are less engaging. Digital-based learning media has also not been optimally utilized in the teaching and learning process. The presence of engaging learning media can make the learning process more enjoyable and effective. This study aims to develop interactive learning media based on Articulate Storyline 3 for the topic of Modern Biotechnology for Grade X MIA students at MAN 1 Padang Lawas. The media development was conducted to determine the validity, practicality, and effectiveness of the developed learning media. This research is a type of Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study resulted in the development of interactive learning media using Articulate Storyline 3 for the topic of modern biotechnology in Grade X MIA at MAN 1 Padang Lawas. The media validity assessment by media experts obtained a score of 84%, categorized as very valid, and by material experts 91%, also categorized as very valid. The practicality test by teachers resulted in a score of 95%, categorized as very practical, while the test by students achieved 90.83%, also categorized as very practical. The effectiveness test based on students' pre-test and post-test results was analyzed using N-Gain, with an average score of 0.70, which falls into the moderate or fairly effective category. Therefore, it can be concluded that the interactive learning media using Articulate Storyline 3 for the modern biotechnology topic in Grade X MIA at MAN 1 Padang Lawas is very valid, very practical, and fairly effective to be used as a teaching medium for modern biotechnology materials for Grade X students.